2022
DOI: 10.1108/ijoem-08-2021-1260
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs' exit strategies and their determinants: the role of perceived exit challenges

Abstract: PurposeThe study aims to investigate whether the perceived problems in exiting a business—as well as the scope of and access to external support—may impact an entrepreneur's decision regarding the exit strategy, that is, the choice between the stewardship and harvest exit strategy.Design/methodology/approachThe authors have collected data from 302 entrepreneurs using a novel survey instrument and subjected the sample to structural equation modeling (SEM) and ordered logit regressions.FindingsThe results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…We also found that entrepreneurs with family succession as the mode of entry were 2.1 times as likely to adopt a family succession exit strategy than entrepreneurs with other entry modes. This result supported and extended the findings of Koładkiewicz et al (2022b), which also suggested a connection between succession as an entry and exit strategy, an expectation echoed in much of the family business succession research. The result also resonates well with the argument that taking over through family succession entails a commitment to the socioeconomic wealth of the family business (e.g.…”
Section: Jsbedsupporting
confidence: 83%
“…We also found that entrepreneurs with family succession as the mode of entry were 2.1 times as likely to adopt a family succession exit strategy than entrepreneurs with other entry modes. This result supported and extended the findings of Koładkiewicz et al (2022b), which also suggested a connection between succession as an entry and exit strategy, an expectation echoed in much of the family business succession research. The result also resonates well with the argument that taking over through family succession entails a commitment to the socioeconomic wealth of the family business (e.g.…”
Section: Jsbedsupporting
confidence: 83%
“…Pengusaha di daerah perkotaan mungkin menghadapi tantangan dalam mengakses tenaga kerja terampil karena persaingan dari bisnis yang lebih besar dan biaya tenaga kerja yang tinggi (Fleischer, 2007). Pertumbuhan perkotaan memberikan tekanan pada area hijau di dalam dan di sekitar kota, yang dapat berdampak negatif pada keanekaragaman hayati dan jasa ekosistem (Koładkiewicz et al, 2022). Pengusaha yang mengandalkan infrastruktur hijau, seperti petani, mungkin menghadapi tantangan dalam mengakses sumber daya ini.…”
unclassified